Visualizations as a tool to increase community engagement in climate change adaptation decision-making - Meredith DeCock-Caspell; Liette Vasseur (Canadian Science Publishing, 2021)
Many barriers to behavioural change exist when it comes to climate change action. A key element to overcoming some of these barriers is effective communication of complex scientific information. The use of visualizations, such as photographs or interactive maps, can increase knowledge dissemination, helping community members understand climatic and environmental changes. These techniques have been utilized in many disciplines but have not been widely embraced by climate change scholars. This paper discusses the utility of climate change data visualization as a tool for climate change knowledge mobilization. This paper draws on the case studying drivers of coastline change of Lake Ontario in the Town of Lincoln, Ontario, Canada. Historical aerial photographs were used to measure the rate of coastline change and visualize vulnerable sections of the coast. To better visualize the changes that occurred over time from a resident viewpoint, selected land-based historical photographs were replicated by taking new photographs at the same locations. These visualization tools can be useful to support the community in developing strategies to adapt to climate change by increasing understanding of the changes and knowledge through social learning. These tools can be generalized to other case studies dealing with community engagement in coastal adaptation efforts.